2016
DOI: 10.1155/2016/9862496
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Effects of Histamine on Primary Human Pterygium Fibroblasts

Abstract: Purpose. It has been confirmed that inflammatory cytokines are involved in the progression of pterygium. Histamine can enhance proliferation and migration of many cells. Therefore, we intend to investigate the proliferative and migratory effects of histamine on primary culture of human pterygium fibroblasts (HPFs). Methods. Pterygium and conjunctiva samples were obtained from surgery, and toluidine blue staining was used to identify mast cells. 3-[4, 5-Dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Although histamine is not considered a growth hormone, it has been shown to have trophic effects on cellular proliferation acting via HRs and subsequently activating secondary signaling pathways 9 , 10 , 32 . In support of our current study, it has been demonstrated that histamine induces proliferation of both human conjunctival fibroblasts and pterygium fibroblasts 33 which was blocked by inhibition of H1HR. In a recent study we found that inhibition of either H1HR or H2HR decreases biliary damage, inflammation and hepatic fibrosis in Mdr2 −/− mice 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Although histamine is not considered a growth hormone, it has been shown to have trophic effects on cellular proliferation acting via HRs and subsequently activating secondary signaling pathways 9 , 10 , 32 . In support of our current study, it has been demonstrated that histamine induces proliferation of both human conjunctival fibroblasts and pterygium fibroblasts 33 which was blocked by inhibition of H1HR. In a recent study we found that inhibition of either H1HR or H2HR decreases biliary damage, inflammation and hepatic fibrosis in Mdr2 −/− mice 2 .…”
Section: Discussionsupporting
confidence: 90%
“…There are many factors promoting the migration of FLSs, such as histamine , protein arginine methyltransferase 5 , growth differentiation factor 9 , Toll‐like receptor 2 and placental growth factor . Leptin, initially identified as a pro‐angiogenic factor , participate in numerous biological processes.…”
mentioning
confidence: 99%
“…We note that all animals received diphenhydramine prophylactically to minimize scratching which can sufficiently severe as to terminate a study. Thus, while there are data showing that histamine (acting through an H1 receptors) can increase fibroblast proliferation ( but see ) and migration (), the results observed with concurrent diphenhydramine dosing of all groups revealed that those animals receiving a continuous delivery displayed greater mass formation than those in the bolus paradigms. In canine studies, fentanyl and alfentanil, unlike morphine, do not degranulate mast cells or produce IT masses .…”
Section: Discussionmentioning
confidence: 95%